Bacterial Seed Endophytes of Domesticated Cucurbits Antagonize Fungal and Oomycete Pathogens Including Powdery Mildew - Khalaf, Eman M.; Raizada, Manish N. (Frontiers in Microbiology, 2018)
The cucurbit vegetables, including cucumbers, melons and pumpkins, have been cultivated for thousands of years without fungicides. However, their seed germination stage is prone to be infected by soil-borne fungal and oomycete pathogens. Endophytes are symbionts that reside inside plant tissues including seeds. Seed endophytes are founders of the juvenile plant microbiome and can promote host defense at seed germination and later stages. We previously isolated 169 bacterial endophytes associated with seeds of diverse cultivated cucurbits. We hypothesized that these endophytes can antagonize major fungal and oomycete pathogens. Here we tested the endophytes for in vitro antagonism (dual culture assays) against important soil-borne pathogens (Rhizoctonia solani, Fusarium graminearum, Phytophthora capsici, Pythium aphanidermatum). The endophytes were also assayed in planta (leaf disk and detached leaf bioassays) for antagonism against a foliar pathogen of global importance, Podosphaera fuliginea, the causative agent of cucurbit powdery mildew. The endophytes were further tested in vitro for secretion of volatile organic compounds (VOCs) known to induce plant defense. Extracellular ribonuclease activity was also tested, as a subset of pathogenesis-related (PR) proteins of plant hosts implicated in suppression of fungal pathogens, displays ribonuclease activity. An unexpected majority of the endophytes (70%, 118/169) exhibited antagonism to the five phytopathogens, of which 68% (50/73) of in vitro antagonists belong to the genera Bacillus and Paenibacillus. All Lactococcus and Pantoea endophytes exhibited anti-oomycete activity. However, amongst the most effective inoculants against Podosphaera fuliginea were Pediococcus and Pantoea endophytes. Interestingly, 67% (113/169) of endophytes emitted host defense inducing VOCs (acetoin/diacetyl) and 62% (104/169) secreted extracellular ribonucleases in vitro, respectively. These results show that seeds of cultivated cucurbits package microbes with significant disease-suppression potential. As seeds can act as vectors for genetic transmission of endophytes across host generations, it is interesting to hypothesize whether humans, when selecting seeds of healthy hosts, may have inadvertently selected for disease-suppressing seed endophytes. As the majority of pathogen-suppressing endophytes belong to Bacillus and Paenibacillus, and since Bacilli are widely used as commercial biocontrol agents of vegetables, we propose that these agents are mimicking the ecological niche established by their endophytic cousins.